Dimerization of a reactive azaacene diradical: synthesis of a covalent azaacene cage [data] - Fuchs, Kathleen; Rivero, Samara M.; Weidlich, Anna; Rominger, Frank; Israel, Noel; Popov, Alexey A.; Dreuw, Andreas; Freudenberg, Jan; Casado, Juan; Bunz, Uwe H. F. (Universität, 2023)
Two series of regioisomeric dicyanomethylene substituted dithienodiazatetracenes with formal para- or ortho- quinodimethane subunits were synthesized and characterized. Whereas the para-isomers (p-n, diradical index y0=0.01) are stable and isolable, the ortho-isomer (y0=0.98) dimerizes into a covalent azaacene cage. Four elongated σ-CC bonds are formed and the former triisopropylsilyl(TIPS)-ethynylene groups transformed into cumulene-units. The azaacene cage dimer (o-1)2 was characterized by X-ray single crystal structure analysis and temperature-dependent infrared (IR), electron paramagnetic resonance (EPR, solid state), nuclear magnetic resonance (NMR) and ultraviolet-visible (UV-Vis) spectroscopies (solution) indicating reformation of o-1.